Factors Influencing the Intention to Purchase Electric Vehicles Using an Extended TPB Model Approach - Hilmi Muhammad Harits Machsar; Rizal Ramdan Padmakusumah; Lutfi Auliarahman (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2026)
Electric vehicles are currently being predicted to become a potential solution towards the air pollution crisis occurring in major cities, such as Bandung. This study investigates factors that influence people’s intention to purchase electric vehicles using Extended TPB approach. The method employed is a descriptive quantitative approach using Partial Least Square–Structural Equation Modeling (PLS-SEM). SmartPLS V3 purposely served as the main analytical tool. The sample population of this study consists of residents of Greater Bandung, with a sample of 137 respondents. The results of the study indicate the influence and significance of Customer Innovativeness and Perceived Benefits on EV Adoption Intention, as well as the roles of Attitude Toward EV Adoption and Perceived Behavioral Control as its mediators